Reducing injection intensity is associated with decreased risk for invasive bacterial infection among high-frequency injection drug users - Salequl Islam; Damani A. Piggott; Alberto Moriggia; Jacquie Astemborski; Shruti H. Mehta; David L. Thomas; Gregory D. Kirk (BMC, 2019)
Abstract Background Bacterial infection is a major cause of morbidity and mortality for persons who inject drugs (PWID). Injection cessation may help abrogate such infections, but maintaining complete cessation is challenging. Limited data exists on the role of reduced injection intensity on invasive bacterial infection risk. We sought to evaluate decreased risk for bacterial infections following cessation and substantive reduction in the injection intensity. Methods Participants were persons in the AIDS Linked to the Intravenous Experience (ALIVE) cohort with initial high-frequency injection drug use (> 1 daily). Pooled logistic regression with generalized estimating equations was used to estimate risk for invasive bacterial infection (pneumonia, endocarditis, or sepsis) among participants achieving complete injection cessation or reduced injection intensity relative to those with sustained high-frequency use. Results Of 2247 study participants with 12,469 paired study visits, complete injection cessation was achieved at 13.5% and reduced injection intensity at 25.5% of study visits. Adjusting for sociodemographics and HIV status, injection cessation was associated with a 54% reduction of bacterial infection at 3 months (odds ratio [OR] 0.46, 95% CI 0.25-0.84) and a 46% reduction at 6 months (OR 0.54, 95% CI 0.36-0.81). Reduced injection intensity was associated with a 36% reduction of infection at 3 months (OR 0.64, 95% CI 0.43-0.96) and a 26% reduction at 6 months (OR 0.74, 95% CI 0.56-0.98). Conclusions Both complete cessation and reduced injection frequency demonstrate substantial benefit in reducing invasive bacterial infection risk among PWID. With high rates of relapse into injection use, targeting sustained reductions in drug use intensity may be a key harm reduction modality for improving clinical outcomes in this population.